Environmental education in teacher training: conceptions and integration (Research, Society and Development, 2022)
Introduction: At present, environmental education is a process that is strictly linked to practice, with the purpose of harmonizing the productive activities of human beings, which is why it is essential to have professionals capable of mitigating environmental destruction, starting with training university, whose future professionals can be multipliers of the information needed to preserve the planet. Objective: This study aims to describe how environmental education has been understood and how it can be integrated into contemporary teacher education. Methodology: a literature review of the narrative type was used, with articles from periodicals and books by specific authors in the area of ​​environmental education, teacher training and teacher training in environmental education based on complex thinking. Results and discussion: It is concluded, therefore, that the development of this narrative review research allowed a broad view of the conception and meanings of environmental education, as well as the importance of pedagogical practice with emphasis on adequate didactics for integration of the environmental theme in formal education.